Distinct modulation of mu and beta rhythm desynchronization during observation of embodied fake hand rotation. (20th August 2021) - Shibuya, Satoshi; Unenaka, Satoshi; Shimada, Sotaro; Ohki, Yukari
Abstract: The rubber hand illusion (RHI) is a phenomenon whereby participants recognize a fake hand as their own. Studies have examined the effects of observing fake hand movements after the RHI on brain sensorimotor activity, although results remain controversial. To address these discrepancies, we investigated the effects of observation of fake hand rotation after the RHI on sensorimotor mu (μ: 8–13 Hz) and beta (β: 15–25 Hz) rhythm event-related desynchronization (ERD) using electroencephalography (EEG). Questionnaire results and proprioceptive drift revealed that the RHI occurred in participants when their invisible hand and fake visible hand were stroked synchronously but not during asynchronous stroking. Independent component (IC) clustering from EEG data during movement observation identified three IC clusters, including the right sensorimotor, left sensorimotor, and left occipital cluster. In the right sensorimotor cluster, we observed distinct modulation of μ and β ERD during fake hand rotation. Illusory ownership over the fake hand enhanced μ ERD but inversely attenuated β ERD. Further, the extent of μ ERD correlated with proprioceptive drift, but not with questionnaire ratings, whereas the converse results were obtained for β ERD. No ownership-dependent ERD modulation was detected in the left sensorimotor cluster. Alpha (α: 8–13 Hz) rhythm ERD of the left occipital cluster was smaller in the synchronous condition than in the asynchronous condition, but α ERD was not correlated with questionnaire rating or drift. These findings suggest that observing embodied fake hand rotation induces distinct cortical processing in sensorimotor brain areas. Highlights: Brain activity during fake hand rotation after RHI was investigated using EEG. Embodied fake hand rotation enhanced sensorimotor mu (μ: 8–13 Hz) rhythm ERD. Beta (β: 15–25 Hz) rhythm ERD was attenuated by embodied fake hand rotation. μ and β ERD were related to hand localization and ownership, respectively. Observing embodied fake hand rotation induces distinct sensorimotor processing.